Analysis of Student Motivation using Chemsketch on Hydrocarbon Topic in SMA Negeri 2 Merauke - Dewi Natalia Marpaung; Jesi Jecsen Pongkendek; Muhammad Fath Azzajjad; Sukirno Sukirno (Journal of Applied Science, Engineering, Technology, and Education, 2021)
The purpose of this research was to analyze student motivation in learning process teach by using Chemsketch. The type of this research is descriptive qualitative research, this research conducted in SMAN 2 Merauke in Papua. Technic that used to get the data using purpose sampling, total population are 28 students in Grade X IPA 2. The data in this research collected using questionnaire that given for student after finish learning process by using software chemsketch on topic hydrocarbon by giving checklist in every item. Based on data analysis, the result only three categorized that got from research, first are 11 student (39.28%) \categorized very high motivation, second are 16 students (57.14%) categorized high motivation , and the third is 1 student (3,5%) categorized medium. From the result showed that the use of chemsketch able to motivate student to learn chemistry especially hydrocarbon topic and for teacher can used as an alternative media for teaching.